Exploring Hornstedtia scyphifera: An extensive multimethod phytochemical investigation reveals the chemical composition and bioactive potential - Jonas Kappen; Andreea David; Klara Pieplow; Annika Wujtschik; Ismail Ware; Dipendu Dhar; Christoph Wagner; Mehdi D. Davari; Katrin Franke; Ludger A. Wessjohann (Springer Nature, 2025)
Hornstedtia scyphifera (J.Koenig) Steud. represents a lesser-known member of the ginger family (Zingiberaceae) that is used in Malaysia as spice and traditional medicine. The phytochemical investigation of leaves from this species utilizing diverse analytical methods has provided comprehensive insights into its chemical profle for the frst time. Headspace gas chromatography-mass spectrometry (HS-GCMS) and GCMS analyses of essential oil and nonpolar extracts verifed α-pinene, camphene, p-cymene, and camphor as main volatile compounds. Metabolite profling of the crude extract by ultra-high-performance-liquid chromatography-high resolution mass spectrometry (UHPLC-HRMS) unveiled terpenoids, favonoids and other phenolics as major compound classes. Isolation and follow-up structure elucidation, involving 1D and 2D NMR, HRMS, UV and CD analysis, yielded two new sesquiterpenoids, (1R,5S,6S,7R,10R)-mustak-14-oic acid (1) and (1R,6S,7S,10R)-6-hydroxy-anhuienosol (2), along with 24 known compounds (seven terpenoids, seven favonoids, ten phenolics), 21 of these never reported for H. scyphifera. Additionally, the crude extract and fractions from the purifcation process were screened for antibacterial and antifungal activity. This is supplemented by an extensive literature research for described bioactivities of all isolated compounds. Our results support and explain previously detected antimicrobial, antifungal and neuroprotective efects of H. scyphifera extracts and provide evidence for its potential pharmacological importance.